Selection on structural allelic variation biases plasticity estimates. (25th March 2019) - Santos, Mauro; Matos, Margarida; Wang, Sheng Pei; Althoff, David M.
Abstract: Wang and Althoff (2019) explored the capacity of Drosophila melanogaster to exhibit adaptive plasticity in a novel environment. In a full‐sib, half‐sib design, they scored the activity of the enzyme alcohol dehydrogenase (ADH) and plastic responses, measured as changes in ADH activity across ethanol concentrations in the range of 0–10% (natural variation) and 16% (the novel environment). ADH activity increased with alcohol concentration, and there was a positive association between larval viability and ADH activity in the novel environment. They also reported that families exhibiting greater plasticity had higher larval survival in the novel environment, concluding that ADH plasticity is adaptive. However, the four authors now concur that, since the study estimated plasticity from phenotypic differences across environments using full‐sib families, it is not possible to disentangle the contributions of allele frequency changes at the Adh locus from regulatory control at loci known to influence ADH activity. Selective changes in allele frequencies may thus conflate estimates of plasticity; any type of "plasticity" (adaptive, neutral, or maladaptive) could be inferred depending on allele frequencies. The problem of scoring sib‐groups after selection should be considered in any plasticity study that cannot use replicated genotypes. Researchers should monitor changes in allele frequencies as one mechanism to deal with this issue.